Youth Employment in the Post-War Northern Economy - Balamurali, N.; Dunusinghe, Priyanga (University of Colombo, 2015)
Unemployment and/or underemployment rate has been identified as one of the causes of the civil war in the Northern Province. Because unemployed youths tend to join forces working against existing socio-economic-political establishments it is of paramount importance to make sure that youth aspirations for employment are met. This study aims to analyse youth employment and unemployment in the post-war Northern Province of Sri Lanka to share some insights regarding these issues. Data was gathered from the Labour Force Survey (LFS) - 2013, conducted by the Department of Census Statistics of Sri Lanka. One of the issues faced by employed young people is the wide-spread prevalence of underemployment.
Keywords: Economic activity, Northern Province of Sri Lanka, Unemployment, Underemployment, Youth